The Metanarrative of Learning Disability - Barden, Owen (Routledge, 2021)
Over the last two centuries, learning disability has become an organising concept: a concept which has radically transformed our sense of what it means to be - or not be - a person. In this chapter, we employ a historiographic methodology to explore a metanarrative which is so powerful and pervasive that it envelops both people with learning disabilities and people without. We draw on archival evidence, our own perspectives, and those of our learning- disabled co-researchers to illuminate three tropes which persist through the metanarrative: that people with learning disabilities are vulnerable, unworthy, and requiring control.
Metanarratives of Disability: Culture, Assumed Authority, and the Normative Social Order
Keywords: Inclusive Society; Disability Inclusion; Intellectual Disability; Advocacy and political participation; Culture; History; Social exclusion